Factors influencing international students’ choice towards universities in Malaysia - Dahari, Zainurin; Abduh, Muhamad (Academic Journals, Inc, 2011)
This paper is aimed to determine factors influencing international postgraduate students in choosing university in Malaysia. Factors such as programs offered, fees, promotion, facilities, prominence, environment, convenience, and scholarship were utilized. A total of 135 international postgraduate students were involved in this study through a direct survey. The percentage technique to extract the information of respondents’ demography was used. Then, the analytic hierarchy process was employed to evaluate the level of importance of each factor. The study found that “programs offered” is the number one factor which influences overall international students’ choice to opt for a postgraduate study in Malaysia universities. There were some differences between students from Asian and Western countries in ranking the importance of those factors. Overall categories of respondents selected “tuition prices”, “facilities”, and the “academic staff prominence” as the preceding factors to follow the “programs offered” factor in a sequential level of importance. In general, the result reflects the awareness of prospective students towards the expected standard of education required from the higher education industry.